Gino Pizza : A small scale business in town - Saifullah Shueb (2015)
Factors of GINO's Pizza succession is by providing strengths and uniqueness in its products offer toward customers. Not to mention the owner himself determinations, efforts, passion, and knowledge in establishing and running his business operation from scratch till become top SME's pizza restaurant in local market in just 3 years of operation.